Virtual and Networked Organizations, Emergent Technologies and Tools First International Conference, ViNOrg 2011, Ofir, Portugal, July 6-8, 2011. Revised Selected Papers - Putnik, Goran D.; Cruz-Cunha, Maria Manuela; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the First International Conference on Virtual and Networked Organizations, Emergent Technologies, and Tools, ViNOrg 2011, held in Ofir, Portugal, in July 2011. The 35 revised full papers presentedwere carefully reviewed and selected from over 60 initial submissions. The papers cover a wide range of topics, such as ubiquitous computing and organizations, cloud computing and architectures, grid computing, human-computer interfaces, serious games, data mining, Web services, cognitive systems, social networks and other emergent IT/IS approaches in various function domains, such as decision support systems, planning, design, control, negotiation, marketing, management and many other, in the context of virtual and networked enterprises and organizations.
Keywords: Computer science; Computer communication systems; Software engineering; Information storage and retrieval; User interfaces (Computer systems).; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Computer Communication Networks; Information Storage and Retrieval; Software Engineering; User Interfaces and Human Computer Interaction; Electronic books